Open Access in Croatia : a study of authors' perceptions - Hebrang Grgić, Ivana (Array, 2009)
The most important participants of scientific communication are scientists. They are both producers and users of scientific information. Publishers, libraries, scientific associations and institutions have to ensure transmission of information but scientists are in the centre of scientific communication. Open Access (OA) to peer-reviewed scientific information is relatively new form of scientific communication and is accepted by a number of worlds’ scientists, universities, libraries and publishers. Numerous surveys of scientists’ involvement in the open access movement have been published throughout the world, but Croatian scientists’ perceptions have never been examined. In this paper, a study of Croatian scientists' perceptions of Open Access movement will be presented. The sample will consist of over 300 Croatian scientists who had published their papers in the last issues of Croatian scientific journals published on the Hrčak portal (portal of Croatian scientific journals) in 2008. Anonymous web questionnaire will be send to the scientists. They will be asked about their publishing experiences – how many scientific papers they publish yearly, are the journals they publish in OA journals, what are reasons for publishing (or not publishing) in OA journals, have they ever self-archived their scientific paper, and if yes - why and where. They will also be asked how they deal with copyright issues while self-archiving. Results will be analyzed altogether as well as according to scientific field. Results will show whether Croatian scientists are familiar with the Open Access movement, whether they practice submitting articles to OA journals and whether they self-archive their papers. Some proposals about future development of Open Access in Croatia will be presented.